World development report 1980 - World Bank (Washington D.C.: The International Bank for Reconstruction and Development/ The World Bank, 1980)
The third World Development Report, 1980 was published at a time of difficulty and uncertainty for the world economy - particularly for the developing countries. the report is divided into: Part I Adjustment and growth in the 1980s. Part II Poverty and human development. Annex World Development Indicators.
rpm 08/02/2019
Ref.
Keywords: Economic Development; Economic history; Economic Policy; Underdeveloped countries